Terminology in South Africa - Alberts, Mariëtta (Lexikos, 1999)
This article deals with terminology and terminography in South Africa. It gives the different meanings attached to the term terminology and describes points of difference between terminology and terminography. It focuses on the dimensions of terminology, namely the cognitive, linguistic and communicative dimension. Since terminologists need to consult with subject specialists, linguists, language users and mother-tongue speakers during different phases of the terminography process, the role of consultation in terminology work is stressed. Various aspects such as cultural differences that need to be taken care of, are discussed. The current South African terminology and terminography situation regarding terminology work undertaken by the National Language Service is examined. Emphasis is placed on the database system being used and the National Termbank. Terminology training also receives attention.Keywords: terminology, terminography, terminologist, terminographer, cognitive dimension, linguistic dimension, communicative dimension, technical dictionary, subject specialist, subject field, subject-oriented, concept-oriented, language-oriented, standardisation, primary term formation, secondary term formation, loan words, borrowing, transliteration, neologism, extension of meaning, total embedding, transference